Plural forms of evidence and uncertainty in environmental health: a comparison of two Chinese cases - Lora-Wainwright, A (Policy Press, 2013)
This paper examines the plural forms of evidence of harm presented by the residents of two Chinese villages affected by severe pollution. Conversely, it scrutinises how and why the antonym to evidence - uncertainty - is emphasised and with what effects. It argues that their uncertainty surrounding environmental health harm is a result of the contexts in which evidence is embedded.